1995
DOI: 10.1111/j.1440-1819.1995.tb01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the task‐related component (P3b) of P3 event‐related potentials

Abstract: Within session and between session reliabilities of the task-related component (P3b) of the P3 measures (amplitude, area and latency) and their habituation across eight sessions separated by 7-10 days, except for an interval of 1 month between the 6th and 7th sessions, were studied based on the difference waves, which were obtained by subtracting the ignored infrequent event-related potentials (ERP) from the target ERP elicited by a standard auditory oddball paradigm with eyes-open or eyes-closed conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…This hypothesis is based on observations that the hemodynamic response to auditory oddball stimuli appears to be robust across samples of participants [Kiehl et al, 2001a,b;Kiehl and Liddle, 2001] and that ERP components elicited by similar stimuli appear to be reproducible over time [Gordon et al, 1986;Maeda et al, 1995;Pollock and Schneider, 1992;Roth et al, 1975;Sinha et al, 1992;Sklare and Lynn, 1984]. In light of the fact that habituation has been observed within and across sessions for ERP components elicited by target and novel stimuli [Friedman et al, 1998;Friedman and Simpson, 1994;Polich, 1989;Polich and McIsaac, 1994;Romero and Polich, 1996;Roth et al, 1975], it was expected that habituation would be observed at some cerebral sites.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Is a Rapidly Prmentioning
confidence: 97%
See 1 more Smart Citation
“…This hypothesis is based on observations that the hemodynamic response to auditory oddball stimuli appears to be robust across samples of participants [Kiehl et al, 2001a,b;Kiehl and Liddle, 2001] and that ERP components elicited by similar stimuli appear to be reproducible over time [Gordon et al, 1986;Maeda et al, 1995;Pollock and Schneider, 1992;Roth et al, 1975;Sinha et al, 1992;Sklare and Lynn, 1984]. In light of the fact that habituation has been observed within and across sessions for ERP components elicited by target and novel stimuli [Friedman et al, 1998;Friedman and Simpson, 1994;Polich, 1989;Polich and McIsaac, 1994;Romero and Polich, 1996;Roth et al, 1975], it was expected that habituation would be observed at some cerebral sites.…”
Section: Functional Magnetic Resonance Imaging (Fmri) Is a Rapidly Prmentioning
confidence: 97%
“…Low-probability task-irrelevant novel stimuli elicit a P3 (i.e., P3a) with a more frontocentral distribution than the canonical parietal distributed P3 (or P3b) elicited by target stimuli. A number of studies have shown that the ERPs elicited by target and novel stimuli are fairly reproducible over time in the same participants [Gordon et al, 1986;Maeda et al, 1995;Pollock and Schneider, 1992;Roth et al, 1975;Sinha et al, 1992;Sklare and Lynn, 1984].…”
Section: Functional Magnetic Resonance Imaging (Fmri) Is a Rapidly Prmentioning
confidence: 98%
“…Auditory event-related potentials (ERPs) in the target detection or`oddball' task in young, normal volunteers apparently are reliable within sessions (Sklare and Lynn, 1984;Polich, 1986;Fabiani et al, 1987;Kinoshita et al, 1995Kinoshita et al, , 1996Maeda et al, 1995) over days (Sklare and Lynn, 1984;Fabiani et al, 1987;Kinoshita et al, 1995Kinoshita et al, , 1996Maeda et al, 1995), months (Lewis, 1984;Karniski and Blair, 1989;Kinoshita et al, 1995Kinoshita et al, , 1996Maeda et al, 1995), and 1.8 years (Segalowitz and Barnes, 1993). Reliable P3 components of the ERP also have been reported among 36 schizophrenics after 3 months (r 0:67±0:85; Hegerl et al, 1988) and, incidentally, in a group of about 25 elderly subjects across 4 tasks (0.44±0.73; Miller et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Polich and Kok (1995), for example, demonstrated that the P3 is sensitive to a variety of biological and environmental factors, such as circadian rhythm, time of year, menstrual cycle, sleep deprivation, and common drugs. Despite these caveats, retest reliability of ERP components elicited by attention tasks (e.g., N1, P2, N2, P3) has been reported in studies of young adults within session (Polich, 1986), over 1-2 weeks (Fabiani, Gratton, Karis, & Donchin, 1987;Maeda et al, 1995), over a 4-week period in young through older adults (Maeda et al, 1995), and in adolescents (Segalowitz & Barnes, 1993), adults (Sandman & Patterson, 2000;Walhovd & Fjell, 2002) and patient populations (Mathalon, Ford, & Pfefferbaum, 2000;Sinha, Bernardy, & Parsons, 1992) over longer periods of 1-2 years.…”
mentioning
confidence: 99%